CONCERNING REFORMATION OF HEALTHCARE SYSTEMS IN NEW SOCIO-ECONOMIC CIRCUMSTANCES OF MARKET ECONOMY - Tretyak, V.P.; Ryzhko, P.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The necessity of improving the Law of Ukraine regarding HealthCare, in correspondence with the modern socio-economic circumstances Ukrainian population vital functions for providing effective and high-quality medicare, principal reorganization and modernization of medical network, staff, new schemes of financing, economic management, technological communications and methods of the Health Care system.